2019
DOI: 10.1016/j.str.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Ubiquitin Variant Inhibitors of USP15

Abstract: Highlights d Tight and selective UbVs target USP15 catalytic and adaptor domains d UbV inhibitors lock the USP15 active site in an inactive conformation d A strand-swapped UbV dimer binds two DUSP domains simultaneously d Linear UbV dimers are potent and specific USP15 inhibitors in cells SUMMARYThe multi-domain deubiquitinase USP15 regulates diverse eukaryotic processes and has been implicated in numerous diseases. We developed ubiquitin variants (UbVs) that targeted either the catalytic domain or each of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 66 publications
5
42
0
Order By: Relevance
“…Interestingly, the domain-swapping of UbV W is reminiscent of that recently reported for other UbVs, one that binds the dimeric RING-RING assembly from the E3 XIAP (UbV.XR) and another that binds the DUSP domain of the DUB USP15 (UbV.15.D) (42,50). Conformational differences between 2 independent crystal structures of UbV.XR suggested flexibility in the β-sheet formed by the domain swap, with different relative orientations varying by 30°for the 2 halves of the dimer.…”
Section: Resultsmentioning
confidence: 71%
“…Interestingly, the domain-swapping of UbV W is reminiscent of that recently reported for other UbVs, one that binds the dimeric RING-RING assembly from the E3 XIAP (UbV.XR) and another that binds the DUSP domain of the DUB USP15 (UbV.15.D) (42,50). Conformational differences between 2 independent crystal structures of UbV.XR suggested flexibility in the β-sheet formed by the domain swap, with different relative orientations varying by 30°for the 2 halves of the dimer.…”
Section: Resultsmentioning
confidence: 71%
“…Our data strongly argue in favor of developing specific USP15 inhibitors, which are only starting to emerge. Interestingly, engineered ubiquitin variants targeting USP15 have recently been reported (Teyra et al, 2019), which may open up to the development of more specific small molecules as well as targeted degraders. More broadly, our study calls for a more systematic effort in understanding how DUBs regulate normal and malignant HSC biology as a critical route towards the selection of effective drug targets and targeted treatment combinations.…”
Section: Discussionmentioning
confidence: 99%
“…A crystal structure of UbV W revealed a domain-swapped dimer with an extended β1 strand that forms an antiparallel β-sheet with the opposite subunit (6). Watson et al (6) note that such swapped dimeric structures have been observed in other UbVs (14,15) and collectively display flexibility across the dimer interface. In UbV W , Gly10 is replaced with tryptophan and situated at the center of the extended β1 strand (6).…”
mentioning
confidence: 89%